2022
DOI: 10.1039/d1ja00375e
|View full text |Cite
|
Sign up to set email alerts
|

Is MIP-OES a suitable alternative to ICP-OES for trace element analysis?

Abstract: Microwave-induced plasma optical emission spectrometry (MIP-OES) has been attracting growing interest since the introduction of a commercial instrument based on a Hammer cavity and resonant iris system (4100 MP-AES, Agilent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…Environmental analysis was included in a review by Fontoura et al 166 (95 references) of recent advances in MIP-AES for trace element determination. It was concluded that the technique could offer a lower-cost alternative to ICP-AES for some applications.…”
Section: Analysis Of Soils Plants and Related Materialsmentioning
confidence: 99%
“…Environmental analysis was included in a review by Fontoura et al 166 (95 references) of recent advances in MIP-AES for trace element determination. It was concluded that the technique could offer a lower-cost alternative to ICP-AES for some applications.…”
Section: Analysis Of Soils Plants and Related Materialsmentioning
confidence: 99%
“…Thus, although MIP-OES provides adequate results, special calibration strategies must be used to ensure accuracy when the calibration standards and samples are considerably different and the external standard calibration method is not efficient, such as matrix-matching calibration (MMC), internal standardization, and standard addition (SA). 14…”
Section: Introductionmentioning
confidence: 99%
“…13 MIP-OES has been attracting interest since a more successful system was released in 2012 by Agilent Technologies, which is based on a Hammer cavity with a resonant iris (4100 MP-AES) and presents some key benecial features, such as operational simplicity, multi-element capacity, automatic optimization for each of the selected lines, low analysis cost, low sample consumption, and low waste generation. 14 Nonetheless, its power is xed at 1.0 kW, while the plasma temperature (between 4220 and 5360 K) and electron number density (n e ) are lower compared with a typical Ar ICP system and consequently it is more susceptible to matrix effects. 13,15 Serrano et al 16 demonstrated that MIP-OES based on a Hammer cavity is susceptible to non-spectral interferences caused by EIEs, such as Ca, and reported that signal suppression or enhancement could be observed for both atomic and ionic lines depending on the wavelength excitation energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5000 K) compared to ICP-OES (up to 10 000 K), makes it susceptible to intense matrix effects. 7–9 Thus, properly chosen operational conditions and calibration strategies are required to circumvent this drawback. 7,8…”
Section: Introductionmentioning
confidence: 99%